Recruiting, retaining, and engaging African American males at selective public research universities : challenges and opportunities in academics and sports - Castenell, Louis Anthony, 1947-; Grantham, Tarek C.; Hawkins, Billy Joe (Emerald Publishing Limited : Information Age Publishing, Inc., 2018)
A problematic, yet uncommon, assumption among many higher education researchers is that recruitment, retention, and engagement of African-American males is relatively similar and stable across all majority White colleges and universities. In fact, the harsh reality is that selective public research universities (SPRUs) have distinctive academic cultures that increase the difficulty of diversifying their faculty and student populations. This book will discuss how traditions and elitist assumptions make it very difficult to recruit, retain, and engage African-American males.The authors will examine these issues from multiple perspectives in three sections that highlight research, policies and practices impacting the experiences of African American males, including Pre-Collegiate Preparation, African American Male Student Athletes, and Undergraduate and Graduate Considerations for African American Male Initiatives.
Keywords: African American male college students.; African American college athletes.; African American men -- Education, Higher.; Academic achievement -- United States.; Universities and colleges -- United States -- Sociological aspects.; Education -- Multicultural Education.; Educational strategies and policy: inclusion.; Educational strategies and policy.; Ethnic groups and multicultural studies.; elektronické knihy; electronic books